Pelatihan Dan Pendampingan Pembuatan Modul Praktikum Berbasis Software Akuntansi - Muhammad Wildan Affan; Dwi Irawan; Tasyahadul Fadlatil Laili; Agnesia Ruli Ayu Rahmawati; Lutfia Fitroh Insani (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
Along with the development of technology that facilitates human activities, as well as in the scope of accounting in the form of a computer-based information system that makes it easier for an accountant to record, process and report financially. One of the accounting software developed in Indonesia is Accurate Accounting which is designed to make it easier for its users and the format used is in accordance with the one in Indonesia. Given the importance of technology, understanding technology is carried out as early as possible, especially for vocational students who are trained to create graduates who are ready to work and can improve their skills. SMK Muhammadiyah 2 Malang as a partner has not made various changes in terms of learning to adapt to the learning of the accounting system using only MYOB, the teaching materials used by teachers of SMK Muhammadiyah 2 Malang still need other references to enrich students' practical experience. Therefore, this study is expected to provide understanding and knowledge about technological advances in the accounting field in the form of accurate accounting software and produce learning modules to improve the quality of learning.